2020
DOI: 10.3389/fonc.2020.572895
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EGFR Mutations in cfDNA and CTCs, and Comparison to Tumor Tissue in Non-Small-Cell-Lung-Cancer (NSCLC) Patients

Abstract: Combined Workflow EGFR in CTCs and cfDNA tissues. Despite the limited size of the patient cohort, results from this non-invasive EGFR mutation analysis are encouraging and this combined workflow represents a valuable means for informing therapy selection and for monitoring treatment of patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 36 publications
0
34
1
Order By: Relevance
“…Discordances between cfDNA in plasma and CTCs may be indicative of tumor heterogeneity that characterizes NSCLC [ 58 ] and also predictive for the resistance mechanisms that occur under selective therapy pressure due to the dominance of T790M wild type clones as it was previously described [ 59 ]. Comprehensive analysis of EGFR mutations in cfDNA and CTCs could be more informative regarding the treatment monitoring of NSCLC patients as it was recently demonstrated in studies that included both liquid biopsy biomarkers [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discordances between cfDNA in plasma and CTCs may be indicative of tumor heterogeneity that characterizes NSCLC [ 58 ] and also predictive for the resistance mechanisms that occur under selective therapy pressure due to the dominance of T790M wild type clones as it was previously described [ 59 ]. Comprehensive analysis of EGFR mutations in cfDNA and CTCs could be more informative regarding the treatment monitoring of NSCLC patients as it was recently demonstrated in studies that included both liquid biopsy biomarkers [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…To select the most appropriate mutation profiling specimens guiding clinical-decision making, it is necessary to perform a comparative study of CTC-derived DNA (CTC-DNA), ctDNA, and tumor tissue DNA (tumor DNA; Table 4). Sundaresan et al [148,149] believe the overall performance of ctDNA is superior to CTCs, but there is still a 20-30% blank that needs to be covered by combination analysis of ctDNA and CTC-DNA in non-small-cell lung cancer, a finding also corroborated in colorectal cancer [150], thoracic cancer [151], metastatic prostate cancer [152], and HCC [153].…”
Section: Limitations and Future Perspectivementioning
confidence: 99%
“…A decrease in ctDNA and CTC levels from the baseline to the second cycle of paclitaxel and bevacizumab in HER2− MBC patients was independent prognostic markers, but with a stronger value for ctDNA when compared to CTCs [ 50 ]. The comprehensive mutational analysis of cfDNA and CTCs revealed the additive value of the analytes [ 14 , 51 ]. Variant analysis in CTCs was shown to be able to identify newly emerging resistance mutations in contrast to cfDNA, where resistance mutations might only be detected after apoptosis of the cells harboring new alterations [ 51 ], thereby highlighting the potential benefits of variant analysis in CTCs over cfDNA.…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive mutational analysis of cfDNA and CTCs revealed the additive value of the analytes [ 14 , 51 ]. Variant analysis in CTCs was shown to be able to identify newly emerging resistance mutations in contrast to cfDNA, where resistance mutations might only be detected after apoptosis of the cells harboring new alterations [ 51 ], thereby highlighting the potential benefits of variant analysis in CTCs over cfDNA. The case study of a HR+ MBC patient with serial liquid biopsies across treatment over 4 years showed the correlation of single CTC and cfDNA copy number variants and mutations, but the authors argued that only the analysis of variants in single CTCs deconvolutes the subclonal evolution in cellular resolution [ 52 ].…”
Section: Discussionmentioning
confidence: 99%